PENGARUH KOMPETENSI PEDAGOGIK GURU TERHADAP MINAT BELAJAR PESERTA DIDIK PADA MASA PANDEMI COVID-19 - Haikal, Rita Fikri; Sami'an, Supendi (THORIQOTUNA: Jurnal Pendidikan Islam, 2021)
This study aims to determine the positive effect of teacher pedagogic competence on students' learning interest during the pandemic covid-19 at Serba Bakti Suryalaya Islamic Junior High School. The method used in this study is a descriptive method through a quantitative approach, with a population of 130 and a sample of 17 people using data collection techniques, namely questionnaires, interviews and observations and usingdata analysis techniques Rank Spearman's. Based on the results of data processing, it was obtained that the influence of teacher pedagogic competence on students' learning interest during the pandemic covid-19 at the Islamic Junior High School Serba Bakti Suryalaya has a positive and significant influence with the sufficient category, it is proven that rs = 0.53 is in the 0.41-0.60 interval and tcount (2,416) is bigger than ttable (1,753). The pedagogic competence of teachers affects students' learning interest during the pandemic covid-19 by 28%, while 72% is influenced by other factors.